Facilitation of holm oak recruitment through two contrasted shrubs species in Mediterranean grazed woodlands - Rolo, Víctor; Plieninger, Tobias; Moreno, Gerardo (Journal of Vegetation Science, 2012)
Question: Regeneration failure and gradual tree dieback are major threats for the persistence of savanna-like grazed oak woodlands. Current research has argued that the scarcity of ‘safe sites’, in particular shrubs, is the main cause of the lack of effective tree recruitment. But can different shrub species be considered as safe sites generally? Do two distinct shrub species, with contrasted life strategies, affect several life stages of tree regeneration in similar ways or do they speciﬁcally inﬂuence the recruitment process? Location: Holm oak woodlands of SW Iberian Peninsula (40°02′ N, 06°06′ W). Methods: We surveyed densities of recently emerged and surviving seedlings as well as small and large saplings over two consecutive years in 40 sites that were independently managed, comparing plots encroached by either Cistus ladanifer (a shallow-rooted shrub, forming dense populations, with reported allelopathic compounds) or Retama sphaerocarpa (a N2-ﬁxing, deep-rooted shrub that forms scattered populations) vs their respective control plots (without shrubs). To assess the effect of mature trees and both shrub species on the performance and survival of recently emerged oak seedlings, we established an acorn sowing experiment in the same surveyed microhabitats (open spaces, shrub, tree and tree–shrub). Results: The survey showed that both shrubs species had a positive effect at early recruitment stages. At later life stages, this effect weakened under Cistus whereas it strengthened under Retama. The acorn sowing experiment showed that both shrub species buffered abiotic conditions and enhanced seedling functioning similarly, but Retama enhanced seedling survival to a higher extent than Cistus. Conclusions: The two shrub species impose a speciﬁc template that is able to affect the long-term dynamics of Mediterranean oak woodlands. Cistus shrubs are effective in protecting seedlings physically against herbivores and facilitate early survival, but may compete with older stages of oak regeneration. In contrast, Retama shrubs exert stronger biological facilitation and guarantee longterm persistence of surviving seedlings. We argue that improved understanding of the effectiveness of different nurse plants and their contrasting factors is of major interest for the conservation and restoration of degraded oak woodlands
Keywords: Cistus ladanifer; Dehesa; nurse plant; Quercus ilex; retama sphaerocarpa; Shrub encroachment